2014
DOI: 10.3922/j.psns.2014.02.05
|View full text |Cite
|
Sign up to set email alerts
|

6-Hydroxydopamine lesions in the medial prefrontal cortex of rats exposed to a peak-interval procedure.

Abstract: Impaired temporal control is symptomatic of several neurological disorders; recently, it has been implicated in schizophrenia. An animal model of schizophrenia using 6-hydroxydopamine (6-OHDA) infused to the medial pre-frontal cortex (mPFC) was employed to examine its effects on temporal control. Twelve rats were trained on a peak-interval procedure (PIP) until stable patterns of behavior were obtained. Rats infused with 6-OHDA responded less during peak trials and their peak functions were flatter than sham r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 25 publications
(63 reference statements)
1
8
0
Order By: Relevance
“…In terms of the history of reinforcement of the rats used in the present study, the same rats were also used in our previous study (Elcoro et al, 2014) in which measures of timing (e.g., peak times) were unaltered after the lesions while overall responding was diminished. This overall decrease in responding was especially marked early after the lesions; with more sessions, partial recovery occurred, not to the extent achieved by the sham group (i.e., back to their prelesion baseline).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In terms of the history of reinforcement of the rats used in the present study, the same rats were also used in our previous study (Elcoro et al, 2014) in which measures of timing (e.g., peak times) were unaltered after the lesions while overall responding was diminished. This overall decrease in responding was especially marked early after the lesions; with more sessions, partial recovery occurred, not to the extent achieved by the sham group (i.e., back to their prelesion baseline).…”
Section: Discussionmentioning
confidence: 99%
“…Acquisition of responding in a PIP as the one used by Elcoro et al (2014) involves eventual decrease in responding (Kaiser, 2008(Kaiser, , 2009 during peak trials given that there is repeated experience with periods of extinction. This pattern of decreased responding during peak trials within the history of reinforcement of the rats may have provided an advantage to performing in a DRL procedure evaluated in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Olton (1989) and Olton et al (1988) observed a later peak. More recently, Elcoro et al (2014) showed that 6-Hydroxydopamine lesions of medial prefrontal cortex led to flatter response distributions, suggesting lower precision.…”
Section: Lesion Studiesmentioning
confidence: 99%